In vitro resolution of adeno-associated virus DNA hairpin termini by wild-type Rep protein is inhibited by a dominant-negative mutant of rep. - Owens, R A (1992)
An adeno-associated virus (AAV) genome with a Lys-to-His (K340H) mutation in the consensus nucleotide triphosphate binding site of the rep gene has a dominant-negative DNA replication phenotype in vivo. We expressed both wild-type (Rep78) and mutant (Rep78NTP) proteins in two helper-free expression systems consisting of either recombinant baculoviruses in insect cells or the human immunodeficiency virus type 1 long terminal repeat promoter in human 293 cell transient transfections. We analyzed nuclear extracts from both expression systems for the ability to complement uninfected HeLa cell cytoplasmic extracts in an in vitro terminal resolution assay in which a covalently closed AAV terminal hairpin structure is converted to an extended linear duplex. Although both Rep78 and Rep78NTP bound to AAV terminal hairpin DNA in vitro, Rep78 but not Rep78NTP complemented the terminal resolution assay. Furthermore, Rep78NTP was trans dominant for AAV terminal resolution in vitro. We propose that the dominant-negative replication phenotype of AAV genomes carrying the K340H mutation is mediated by mutant Rep proteins binding to the terminal repeat hairpin.